2018
DOI: 10.3389/fmicb.2018.00899
|View full text |Cite
|
Sign up to set email alerts
|

A Mosaic of Geothermal and Marine Features Shapes Microbial Community Structure on Deception Island Volcano, Antarctica

Abstract: Active volcanoes in Antarctica contrast with their predominantly cold surroundings, resulting in environmental conditions capable of selecting for versatile and extremely diverse microbial communities. This is especially true on Deception Island, where geothermal, marine, and polar environments combine to create an extraordinary range of environmental conditions. Our main goal in this study was to understand how microbial community structure is shaped by gradients of temperature, salinity, and geochemistry in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 65 publications
8
45
0
1
Order By: Relevance
“…Indeed, in a previous work, we detected only archaeal 16S rRNA sequences in FBA sample using Illumina sequencing technique (Bendia et al, 2018 …”
Section: Estimated Number Of Total Bacterial Cells Through Qpcrmentioning
confidence: 92%
See 1 more Smart Citation
“…Indeed, in a previous work, we detected only archaeal 16S rRNA sequences in FBA sample using Illumina sequencing technique (Bendia et al, 2018 …”
Section: Estimated Number Of Total Bacterial Cells Through Qpcrmentioning
confidence: 92%
“…Carrión et al (2011) isolated eight strains of marine sediments from the island, belonging to the genera Pseudomonas, Marinobacter, and Shewanella, and one of these strains was classified as a new species, proposed Pseudomonas deceptionensis. In a previous work, we reported the presence of several extremophiles-related sequences (psychrophiles, thermophiles, hyperthermophiles, and halophiles) among extreme temperature gradients in Deception (Bendia et al 2018). However, since only 16S rRNA gene sequences were evaluated, it was not possible to know if these extremophiles were viable in those conditions.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The majority of these previous studies have focused on nonpolar thermal ecosystems, where the temperature range is narrower than in polar volcanoes; the exception is a study of deep-sea hydrothermal vents, in which the contrasting temperatures are created by the contact of heat with the surrounding cold seawater (with temperatures 0-4 o C). Indeed, the Deception communities from fumaroles have similar members (Bendia et al, 2018b) to those found in deep-sea hydrothermal vents (e.g. Dick, 2019;Nakagawa et al, 2006;Takai et al, 2001), which suggests that, regarding differences in pressure (and other environmental effects), the wide temperature range typical of polar volcanoes and deep-sea hydrothermal vents can act as a strong selective pressure that favors (hyper)thermophilic specialists capable of thriving in high temperatures but that can also tolerate the cold surroundings.…”
Section: Introductionmentioning
confidence: 90%
“…To compare our results with the study performed by Bendia et al (2018b), we used the same dataset and DNA extractions as a template for the metagenomics. Due to low DNA mass even after several concentration efforts, extracted DNA was subjected to multiple displacement amplification (MDA) using the illustra GenomiPhi V2 DNA amplification kit (GE Healthcare, Piscataway, NJ, USA), following the manufacturer's instructions.…”
Section: Dna Extraction and Metagenomic Sequencingmentioning
confidence: 99%
See 1 more Smart Citation